Pengaruh Audit Capacity Stress dan Remote Audit Terhadap Kualitas Audit oleh Auditor Kantor Akuntan Publik - Yossi Septriani; Della Tri Mutia; Afridian Wirahadi Ahmad (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This quantitative study investigates the impact of audit capacity stress and remote auditing on the audit quality of auditors in public accounting firms. Using a primary data approach, structured questionnaires were administered to 112 auditors across different locations, including DKI Jakarta, Banten, West Java, West Sumatera, and Riau provinces. Respondents were selected via purposive sampling, specifically targeting those with experience managing minimal five clients. Data were measured on a five-point Likert scale and analyzed using multiple linear regression via SPSS version 25. The empirical results show that audit capacity stress exerts no significant influence on audit quality. Conversely, remote auditing was found to have a positive and statistically significant effect on audit quality. These findings indicate that audit quality is more strongly influenced by the efficacy of technology-based implementation and digital adaptation than by workload capacity pressures. Consequently, the study suggests that the integration of robust remote auditing frameworks is a more critical determinant of professional standards than individual auditor capacity constraints in the contemporary auditing landscape.